Bond strength of a resin-based composite to aged Biodentine using different adhesive strategies (Annals of Medical Research, 2021)
Aim: The objective of the present study was to evaluate the microshear bond strength (µSBS) of resin composite to Biodentine, which is a bioactive dentin substitute after aging periods using different adhesive systems.Material and Methods: One hundred and eighty cylindrical shaped blocks with a cavity of 5-mm in diameter and 2-mm in depth were fabricated from a self-cured acrylic. The Biodentine was mixed and loaded into the cavities. The prepared specimens were divided into 3 groups in accordance with aging periods (12-min; 24-h; 1-week). After the aging, each group was allocated to 6 subgroups: subgroup 1, no adhesive (control); subgroup 2, two-step etch-and-rinse adhesive; subgroup 3, two-step self-etch adhesive; subgroup 4, one-step self-etch adhesive; subgroup 5, universal adhesive in self-etch mode; subgroup 6, universal adhesive in etch-and-rinse mode. After adhesive application, resin composite cylinder was applied over Biodentine surface to assess µSBS. The µSBS was evaluated using a µSBS tester and failure modes were at 30× magnification. Statistical analyses were performed using two-way ANOVA and Tukey tests.Results: Biodentine shows lower µSBS at the 12-min. There were no considerable differences between 24-h and 1-week aging periods. Universal adhesive exhibited the highest bond strength values.Conclusion: Twenty-four hour waiting for the final restoration after the Biodentine placement could be useful to obtain better bond strength. In addition, highest µSBS values were detected for the universal adhesive irrespective to the application mode.